“EVERYTHING STARTS HERE…”: REZHITSK–PSKOV ORIGINS OF THECREATIVE PERSONALITY OF YURY TYNIANOV - Razumovska, Aīda; Cepina, Anastasija; Jefimovs, Ņikita (Via Latgalica, 2014)
Yury Tynyanov is an outstanding scientist, writer, translator, one of the founders of the formal school in literary criticism. The article is devoted to the role of two cities – Rēzekne and Pskov – in the destiny of Tynyanov. These are place, where the writer spent his childhood and youth. Kaverin’s statement refers to both cities: “Tynyanov paid attention to his childhood, which was following him slowly but steadily.”Tynyanov’s memoirs, reminiscences of his friends and contemporaries provide an interesting material for analysis. Child’s impressions are reflected in writer’s autobiography. It is connected with daily life of Rezhitsa (Rēzekne) and its inhabitants. Primarily, author’s attention was drawn to people – the representatives of different nationalities and social stratums, who retained their cultural traditions and mode of life: “The town was small, hilly and very different.On the hill there were the ruins of Livonian castle, Jewish alleys were below, and beyond the river there was a schismatic skit. At the same time there lived Jews, Belarusians, Great Russians and Latvians, and there were several centuries and countries. Old Believers were like Surikov archers. In the skit there was celebrated a wedding on rabid horses.Russian people of the 17th century were walking there; old men were wearing long coats, wide-brimmed hats; beards were like sharp, long icicles. Drunkenness was archaic and often ended up with riding.”Tynyanov strived to understand thoughts, characters and essence of people. Drawing portraits of townspeople from memory, the writer noted some details, which are important for understanding human’s nature. These descriptions can be called psychological.With such a desire to cognize human’s soul it is no wonder that little Tynyanov mostly was interested in people, who were out of the crowd, standing below the norm not only socially, but also psychologically. Rezhitsa gave him amazing material for observation: “There were a lot of crazy and eccentric people in the town. They amused everyone. One young Jew stamped his feet in front of the photoshop’s showcase which he stared at, yelling: “My dear, look straight at me!” A crazy woman was driving a brood of her children – they grew in number from year to year. Went without Karamazov.”Tynyanov described a lot of astonishing people, remembering his hometown. He remembered the names of many of them: Kolia Topolev, who wasted all money on cabs and became a tramp, Mishka Posadskii – terrible, one-handed, looked like a cautious, confident beast of unknown breed, and Crazy Nikolay – so exact that hostess checked on him, whether it is time to start preparing porridge.From his childhood’s observations Tynyanov began his way to become one of the most extraordinary researchers and a peerless writer. He had an amazing ability to take the shape of another person like an actor. He could see what he feels, what he is thinking about and what the matters of his behaviour are. He could become this person for a while, whether it is tramp or Pushkin himself or Griboyedov. Taking into consideration the fact, which can be observed in reality or taken from a historical document, Tynyanov was able to go further, to go under the surface, to feel intuitively the condition of a person. He formulated his method this way: “I start where the document ends.”The role of Pskov in Tynyanov’s life has also played a significant role, because places had always had a great impact on the writer and had shaped the identity, future, as well as the literary taste of the philologist. In Pskov, during the years of studying at school, Tynyanov gained his first friends, began to learn Russian and foreign literature. Everyday life of the city itself, i. e., its weekdays and holidays influenced the philologist’s future: “Since that time I got to know Russian province.” A particular attention in the autobiography is paid to prisons and convicts, but still the determining factor in the perception of the city is an amazing atmosphere of intellectual and artistic freedom.